Bioencapsulation Artemia with Bacillus subtilis and Sodium Alginate on Total Hemocyte and Survival of Litopenaeus vannamei Infected with Vibrio parahaemolyticus - Anggraini Widihastuti; Woro Hastuti Satyantini (Universitas Airlangga, 2023)
Disease control in shrimp culture is mostly done by using probiotics such as B. subtilis. Immunostimulants are also widely used to improve the white shrimp immune system. One of the immunostimulants that can be used is sodium alginate. The purpose of this study was to determine the effect of bioencapsulation of Artemia with the combination of B. subtilis and sodium alginate on total hemocytes and the survival of white shrimp infected with V. parahaemolyticus. This study used a completely randomized design (CRD) with 5 treatments and 4 replications. Hemocyte total and survival were measured at H0, H7 after bioencapsulation, H9 one day post-infection, and H16 seven days post-infection. The results showed that the total hemocytes H7 and H9 in treatment P3 were significantly different (p<0.05) against all treatments, while the survival of white shrimp in H9, P1 and P3 treatment was not significantly different (p>0.05), to the treatment of K- and P2. The conclusion of this study was that the bioencapsulation of Artemia with the combination of B. subtilis and sodium alginate could increase total hemocytes and the survival of PL white shrimp infected with V. parahaemolyticus.